1990
DOI: 10.1152/ajpgi.1990.258.1.g122
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin inhibition of cholinergic myenteric neurons in canine antrum

Abstract: Neurokinins regulate gastrointestinal motility by interacting with receptors on both muscle layers and on myenteric plexus neurons. To determine if specific neurokinin (NK) receptor agonists can mediate inhibitory effects on myenteric neurons, we studied the effect of the NK-1 agonist substance P methylester (SPME) and the putative endogenous NK-2 receptor ligand neurokinin A (NKA) on [3H]acetylcholine [( 3H]ACh) release induced by electrical field stimulation from muscle strips cut from the canine gastric ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…We have found that rather than involving (Mayer et al, 1990;Rangachari et al, 1990). Moreover, exogenous eicosanoids mimic neurokinin actions to produce mechanical hyperalgesia (Ferreira and Nakamura, 1979; Naka- mura-Craig and Smith, 1989), to inhibit acetylcholine release from gastric myenteric plexus (Mayer et al, 1990), to resist gastric mucosal injury after noxious challenge (Whittle and Lopez-Belmonte, 1991), and to enhance airway mucus secretion (Rogers et al, 1989;Jacquot et al, 1990). Finally, adenylyl cyclase activation could underly neurokinin-stimulated striatal dopamine release (Reid et al, 1990) because this response is mimicked by treatments raising cAMP levels (Santiago and Westerink, 1990).…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…We have found that rather than involving (Mayer et al, 1990;Rangachari et al, 1990). Moreover, exogenous eicosanoids mimic neurokinin actions to produce mechanical hyperalgesia (Ferreira and Nakamura, 1979; Naka- mura-Craig and Smith, 1989), to inhibit acetylcholine release from gastric myenteric plexus (Mayer et al, 1990), to resist gastric mucosal injury after noxious challenge (Whittle and Lopez-Belmonte, 1991), and to enhance airway mucus secretion (Rogers et al, 1989;Jacquot et al, 1990). Finally, adenylyl cyclase activation could underly neurokinin-stimulated striatal dopamine release (Reid et al, 1990) because this response is mimicked by treatments raising cAMP levels (Santiago and Westerink, 1990).…”
Section: Introductionmentioning
confidence: 47%
“…These are distributed differentially throughout both the central nervous system (CNS) and peripheral tissues where they regulate a wide variety of physiological processes including smooth muscle contraction, inflammation, perception of pain, secretion, neurotransmission, and proliferation (Nilsson et al, 1985;Grandordy et al, 1988;Nakamura-Craig and Smith, 1989;Rogers et al, 1989;Mayer et al, 1990;Reid et al, 1990). Neurokinin actions are mediated by three pharmacologically distinct cell-surface receptors classified as NK-1, NK-2, and NK-3 that display limited selectivity toward SP, NKA, and NKB, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There is little information available on prostaglandins contributing to tachykinin-induced biological responses in the gastrointestinal system. Tachykinins might induce the formation of prostaglandins in the chicken gut through indirect mechanisms, since VIP and acetylcholine enhanced prostaglandin synthesis in the mammalian gastrointestinal tract (Sanders 1978;Mayer et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Tachykinins have been reported to exert similar effects at myenteric neurons of the mammalian gut, by acting mostly on neuronal NK 3 receptors (e.g. Kilbinger et al 1986;Guard and Watson 1987;Laufer et al 1988;Fox and Morton 1991;Emonds-Alt et al 1995) and possibly on NK 1 receptors (Guard and Watson 1991), although evidence has also been provided for an inhibitory NK 1 receptor-mediated effect of tachykinins on electrically induced release of Ach from gastric (Mayer et al 1990) and enteric (Kilbinger et al 1986;Löffler et al 1994) neurons. Our results extend the former observations to the biliary system, and also provide evidence for the involvement of NK 1 and NK 2 receptors, along with NK 3 receptors, as neuronal mediators of tachykinin effects.…”
Section: The Role Of Tachykininsmentioning
confidence: 99%